2021
DOI: 10.1186/s40463-021-00493-2
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Rhinology Working Group consensus statement: Biologic therapies for chronic rhinosinusitis

Abstract: Background Recent evidence suggests that biologic therapy with targeted activity within the Type 2 inflammatory pathway can improve the clinical signs and symptoms of chronic rhinosinusitis with nasal polyposis (CRSwNP). There remains a population in CRSwNP that despite medical therapy and endoscopic sinus surgery have persistent signs and symptoms of disease. Therefore, biologics, monoclonal antibody agents, could be beneficial therapeutic treatments for these patients. There have been eight r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 26 publications
0
43
0
Order By: Relevance
“…The Canadian Rhinology Working Group recommends that biologic therapies for chronic rhinosinusitis be considered only for patients who have failed medical therapy and have undergone sufficient sinus surgery or for patients who cannot undergo sinus surgery and have failed medical therapy [ 6 ]. However, at this time, access to dupilumab for Canadian patients and specifically in the province of Ontario, remains limited to only a fraction of those with private insurance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Canadian Rhinology Working Group recommends that biologic therapies for chronic rhinosinusitis be considered only for patients who have failed medical therapy and have undergone sufficient sinus surgery or for patients who cannot undergo sinus surgery and have failed medical therapy [ 6 ]. However, at this time, access to dupilumab for Canadian patients and specifically in the province of Ontario, remains limited to only a fraction of those with private insurance.…”
Section: Discussionmentioning
confidence: 99%
“…Given the inexperience of clinicians managing patients with CRSwNP, the Canadian Rhinology Working Group produced a white paper providing guidance to treating physicians, both in Canada and internationally, when considering monoclonal antibody therapy for patients with CRSwNP [ 6 ]. Despite this guidance, questions about real-world efficacy of the processes for accessing treatment and treatment related outcomes in comparison to clinical trial results, are a concern for any new therapy [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been have reported that all three biologics, dupilumab, omalizumab, and mepolizumab, can reduce the size of nasal polyps and improved nasal symptoms, with dupilumab having the best efficacy and omalizumab and mepolizumab being equivalent, and all three having similar effects on improving quality of life ( 41 , 42 ). These effects decrease use of oral glucocorticoids and need for reoperation, thereby providing new treatment for refractory CRSwNP ( 39 , 40 ). However, application of biologic agents in the clinical setting for CRS treatment has three main limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Any co-management of asthma further complicates medical management by increasing the dosage and administration of steroids, in this case preferably oral, increasing the risk of adverse side effects and the potential for antibiotic prophylaxis and bacterial resistance [ 24 ].…”
Section: Discussionmentioning
confidence: 99%